Development of silk fibroin/nanohydroxyapatite composite hydrogels for bone tissue engineering. (June 2015) - Ribeiro, Marta; de Moraes, Mariana A.; Beppu, Marisa M.; Garcia, Mónica P.; Fernandes, Maria H.; Monteiro, Fernando J.; Ferraz, Maria P.
Graphical abstract: Highlights: Development of SF/nanoHA composite hydrogels with the purpose of filling small bone defects. Novel and innovative method to produce composite hydrogels in few minutes. Macro/microporous structure with bioactive particles uniformly dispersed. This composite combine mechanical properties, porosity and biological performance. Abstract: This work presents a novel composite hydrogel consisting of silk fibroin (SF) and nanohydroxyapatite (nanoHA) prepared by a new and innovative method using ethanol as gelling agent capable of forming hydrogels in few minutes. The properties of the composite material, such as the microstructure as well as the chemical and physical properties were studied. Moreover in␣vitro studies of osteoblastic citocompatibility were performed. The microporosity and macroporosity obtained combined with interconnected porous structure and a uniform dispersion of nanoHA particles throughout the fibroin matrix makes composite hydrogel suitable for bone regeneration. The compression modulus of composite hydrogels was increased as the nanoHA concentration increased from 10 to 15 wt.% and the water uptake ability of these materials decreased with the incorporation of nanoHA. The metabolic and alkaline phosphatase activities of osteoblastic cells were improved with the incorporation of nanoHA in the SF matrix providing a more promising material for bone tissue engineering.